A new species of Apenesia (Hymenoptera, Bethylidae) from India, a parasitoid of coffee white stem borer Xylotrechus quadripes (Coleoptera, Cerambycidae) - Azevedo, C. O.; Waichert, C. (Zootaxa, 2006)
Apenesia sahyadrica sp. nov. is described and illustrated based on specimens from Arabic coffee infested with the white stem borer Xylotrechus quadripes Chevrolat. The new species is endemic to Western India and is under laboratory rearing in Coffee Research Station Chikmagalur for biocontrol of this pest. The new species is compared with other related species of Oriental Apenesia.